Peranan Kejaksaan Menangani Perkara Tindak Pidana Bidang Perlindungan dan Pengelolaan Lingkungan Hidup: The Role of the Prosecutor's Office in Handling Criminal Cases in the Field of Environmental Protection and Management - Bahar Elfudllatsani; Lubis, Muhammad Ikhsan (Pusat Strategi Kebijakan Penegakan Hukum, Kejaksaan Agung, 2025)
The development of attention and awareness of the world community is influenced by the development of science related to the impacts and serious threats that arise for human health and the environment. The new paradigm is that environmental destruction is considered a form of human rights violation. Human rights are not only about protecting